Enhancing flexural resistance in hot mix asphalt: a study of effects of wire mesh on load-bearing capacity - Romaynoor Ismy; Suhaimi Suhaimi; Raden Dedi Iman Kurnia; Richard Mareno (Institute of Advanced Engineering and Science, 2024)
In transportation engineering, road pavement is commonly categorized as either flexible pavement or rigid pavement. The pavement demonstrates a distinct capacity to endure a variety of loads, including compressive and tensile loads. The capacity to endure compressive and tensile forces is extremely important, especially in the field of pavement construction, as it ensures both the longevity and the safety of the pavement. The objective of this study was to evaluate the capacity of hot mix asphalt to endure compressive and tensile pressures. The experimental methodology employed four different wire mesh deployment configurations on hot asphalt mixtures, utilizing three-point flexural test equipment. The data indicates the most effective method for mimicking hot mix asphalt involves adding a wire mesh layer at a depth of 30 mm below the surface of the experimental specimen. The particular modeling method showed a measurement of flexural resistance up to 291.85 kN. The study's findings indicate that the hot asphalt mixture exhibits a state of balance in its capacity to endure both compressive and tensile pressures. Incorporating a wire mesh layer within the middle section of the hot asphalt mixture has been perceived to enhance its ability to withstand tensile loads, hence improving its overall performance.